The effects of microbial fermentation on antibacterial activity of seaweed (Kappaphycus alvarezii) extracts - M.N, Norakma; A.H., Zaibunnisa; Razarinah W.A.R, Wan (International Journal of Engineering and Technology, 2018)
In the present study, Kappaphycus alvarezii one of the most abundant red algae in Malaysia was fermented with Aspergillus oryzae at 30oC for six days with 70% initial moisture content. Total phenolic content and antibacterial activity of fermented seaweed extracts was determined and compared to the non-fermented counterparts. It is found that total phenolic content increased as the fermentation progressed. Green variety fermented for four days exhibited the highest phenolic content (10.022 mg GAE/g). Meanwhile, fermented seaweed extracts tested for antibacterial activity showed that antibacterial activity of fermented seaweed against six different bacteria increased as the fermentation day increased. Green and Yellow variety fermented for six days demonstrated the highest antimicrobial activity (7 mm) against MRSA and Salmonella respectively. pH of fermented seaweed extracts increased with the increase of fermentation day and it might be related with the antimicrobial susceptibility which greater at increasing pH value.Â Â